^{2}X - tan

^{4}X =- 3

^{2}X + 1 - Tan

^{4}X = -3

^{4}X + Tan

^{2}X + 1 + 3 = 0

^{4 }X - Tan

^{2}X - 4 = 0

^{2 }X - 4 ) ( Tan

^{2}X +1 ) =0

^{2}X = 4 Tan

^{2}X +1 = 0 ( Has no acceptable answer.)

sec^2 x - tan ^4 x = 3 Solve for x

Tutors, sign in to answer this question.

Parviz F. | Mathematics professor at Community CollegesMathematics professor at Community Colle...

Just need to convert the Trigonometric function to one function like tanX

Sec^{2}X - tan^{4} X =- 3

Tan^{2} X + 1 - Tan^{4} X = -3

- Tan^{4} X + Tan^{2} X + 1 + 3 = 0

Tan^{4 }X - Tan^{2} X - 4 = 0

( Tan^{2 } X - 4 ) ( Tan^{2} X +1 ) =0

Tan ^{2} X = 4 Tan^{2} X +1 = 0 ( Has no acceptable answer.)

Tan X = ± 2 X = 63.4 ° X = - 63.4°

X = 243.7° X = 153.4°

These are answers between range of 0 < X < 360°

For all possible answer add 2n( 360° ) to each 4 X values.

Note that 3 was changed to -3, for plus 3 there is no real solution.

Michael F. | Mathematics TutorMathematics Tutor

But:

Sin^{2} X + Cos^{2}X = 1

Sin^{2} X / Cos^{2 }X + 1 = Sec^{2} X

1 + Tan^{2 }X = sec^{2} X

So , substitution in 2nd line is correct.

Already have an account? Log in

By signing up, I agree to Wyzant’s terms of use and privacy policy.

Or

To present the tutors that are the best fit for you, we’ll need your ZIP code.

Your Facebook email address is associated with a Wyzant tutor account. Please use a different email address to create a new student account.

Good news! It looks like you already have an account registered with the email address **you provided**.

It looks like this is your first time here. Welcome!

To present the tutors that are the best fit for you, we’ll need your ZIP code.

Please try again, our system had a problem processing your request.

Alexis G.

All-Subject/Test Prep Tutor, Specializing in Language Instruction

$11.25 per 15 min

View Profile >

Nathan G.

University Certified Online Teacher of ESL American English

$9.75 per 15 min

View Profile >

Todd S.

Experienced Spanish tutor

$11.25 per 15 min

View Profile >

## Comments

^{4}X + Tan^{2}X + 1 - 3 = 0 copied from your solution becomes^{4}x+tan^{2}x-2=0 or tan^{4}x-tan^{2}x+2=0 whose discriminant is -7